Complete genome sequence of Parvibaculum lavamentivorans type strain (DS-1T). Issue 3 (November 2011) - Schleheck, David; Weiss, Michael; Pitluck, Sam; Bruce, David; Land, Miriam; Han, Shunsheng; Saunders, Elizabeth; Tapia, Roxanne; Detter, Chris; Brettin, Thomas; Han, James; Woyke, Tanja; et al.
Abstract Parvibaculum lavamentivorans DS-1T is the type species of the novel genusParvibaculum in the novel familyRhodobiaceae (formerlyPhyllobacteriaceae ) of the orderRhizobiales ofAlphaproteobacteria . Strain DS-1T is a non-pigmented, aerobic, heterotrophic bacterium and represents the first tier member of environmentally important bacterial communities that catalyze the complete degradation of synthetic laundry surfactants. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 3, 914, 745 bp long genome with its predicted 3, 654 protein coding genes is the first completed genome sequence of the genusParvibaculum, and the first genome sequence of a representative of the familyRhodobiaceae .